Ideational Leadership in German Welfare State Reform : How Politicians and Policy Ideas Transform Resilient Institutions - Stiller, Sabina (2009)
The author of this innovative study argues that key politicians and their policy ideas, through "ideational leadership", have played an important role in the passing of structural reforms in the change-resistant German welfare state. This argument is based on in-depth case studies of individual reforms in health care, pensions and unemployment insurance since the early 1990s as well as a concise analysis of recent changes in family policy. Stiller concludes that Germany, traditionally a Bismarckian welfare state, has embarked on a path of 'hybridisation' that confronts German politics with growing societal divisions. This thought-provoking title is highly recommended for policymakers, scholars and students interested in the past and future reforms of the German welfare state, leadership, and the role of ideas in policymaking. Hoe worden ingrijpende hervormingen in de alom als weerbarstig beschouwde Duitse welvaartsstaat doorgevoerd? Dit boek betoogt dat het 'ideeëngerichte leiderschap' van vooraanstaande politici in belangrijke mate invloed heeft uitgeoefend op de institutionele veranderingen in het sociaal beleid. Sabina Stiller baseert haar bevindingen op diepgaande case studies van afzonderlijke hervormingen in de gezondheidszorg, pensioenen en werkloosheidsverzekering sinds het begin van de jaren '90 van de vorige eeuw. De auteur biedt een langetermijnperspectief op beleidshervormingen binnen deze gebieden, maar ook op gezinsbeleid waar recentelijk aanzienlijke hervormingen hebben plaatsgevonden. Ideational Leadership in German Welfare State Reform concludeert dat deze 'Bismarckiaanse' verzorgingsstaat zich op een pad van 'hybridisering' bevindt, die de Duitse politiek confronteert met groeiende sociale ongelijkheid. Dit boek is onmisbaar voor studenten, academici en mensen die geïnteresseerd zijn in de rol van beleidsideeën, leiderschap en de recente hervormingen van de Duitse welvaartsstaat.